Use of Marine Microorganisms in the Production of Bioactive Materials for the Pharmaceutical Industry - Fetronela Rambu Bobu; Ivan Junius Mesak (CV. Get Press Indonesia, 2024)
The global pharmaceutical industry is constantly looking for new resources that can be used to develop bioactive ingredients to produce more effective and innovative medicines. One resource that has attracted the attention of researchers is marine microorganisms (UGM, 2017; Wiganti, 2022). The ocean, which covers more than 70% of the Earth's surface, is an ecosystem rich in biodiversity, including microorganisms that are unique and rarely found in terrestrial environments. This research aims to explore and identify marine microorganisms that have potential in the production of bioactive materials for pharmaceutical applications. Based on the results of this study, only Extract I showed significant inhibition against Staphylococcus aureus, while Extract II had almost no inhibition. Table 2 shows the results of the study indicating that the inhibition of seaweed extracts was absent. Gracillaria sp. seaweed extracts evaporated through a rotary vacuum evaporator and seaweed extracts evaporated through an oven had no inhibition. This study showed that bioactive compounds prepared through extraction using vacuum evaporator had greater inhibition of Staphylococcus aureus. This suggests that marine microorganisms can be a source of bioactive ingredients for the pharmaceutical industry.